Evidence for Degradation of the Chrome Yellows in Van Gogh's Sunflowers: A Study Using Noninvasive In Situ Methods and Synchrotron‐Radiation‐Based X‐ray Techniques. Issue 47 (20th October 2015) - Monico, Letizia; Janssens, Koen; Hendriks, Ella; Vanmeert, Frederik; Van der Snickt, Geert; Cotte, Marine; Falkenberg, Gerald; Brunetti, Brunetto Giovanni; Miliani, Costanza
Abstract: This paper presents firm evidence for the chemical alteration of chrome yellow pigments in Van Gogh's Sunflowers (Van Gogh Museum, Amsterdam). Noninvasive in situ spectroscopic analysis at several spots on the painting, combined with synchrotron‐radiation‐based X‐ray investigations of two microsamples, revealed the presence of different types of chrome yellow used by Van Gogh, including the lightfast PbCrO4 and the sulfur‐rich PbCr1− x S x O4 ( x ≈0.5) variety that is known for its high propensity to undergo photoinduced reduction. The products of this degradation process, i.e., Cr III compounds, were found at the interface between the paint and the varnish. Selected locations of the painting with the highest risk of color modification by chemical deterioration of chrome yellow are identified, thus calling for careful monitoring in the future. Abstract : Why is the yellow darkening? Firm evidence that chrome yellow pigments darken through the Cr VI →Cr III reduction is provided by the use of complementary analytical techniques. Different types of chrome yellow, that is, the lightfast PbCrO4 and the light‐sensitive sulfur‐rich PbCr1− x S x O4 ( x ≈0.5), are shown to be present, and spots of the painting with the highest risk of color change have been identified.